Soft Skills or Hard Cash? : What Works for Female Employment in Jordan? - World Bank (World Bank, Washington, DC, 2017)
Jordan faces extremely high levels of youth unemployment: 19 percent of male and 48 percent of female youth between the ages of 19 to 24 years old want to work but can't find jobs. For men, the transition from school to work is slow (on average 15 months), but for women the school to work transition often never takes place. In this context of high female unemployment and low female labor force participation, the Jordanian government, requested the World Bank's support to develop an employment pilot targeting female community college graduates in 2009. This pilot is part of a broader technical assistance program supporting the reform of the public community college system in Jordan. The objective of the Jordan New work Opportunities for Women (NOW) pilot was to increase female labor force participation and help women gain real world job experience. In particular, the hope was to improve information between firms and potential workers, create an opportunity to change negative stereotypes from firms and young women about women's role in the labor market, and improve soft skills and communication. Overall, the objectives of the Jordan NOW pilot were to increase labor force participation and to give young female graduates a chance to accrue some work experience.